Blastomycosis In A Male Dog - Vairamuthu, S.; Pazhanivel, N.; Jeyaraja, K.; Balachandran , C. (Indian Journal of Veterinary Sciences and Biotechnology, 2012)
Blastomyces dermatitidis, a thermal dimorphic fungus is the etiologic agent of blastomycosis in dogs and cats. It exists as a mould in the soil, and as a broad-based, budding yeast form in tissues or when cultured at body temperature (Bateman, 2002). The present case report puts on the record the occurrence of blastomycosis in a non-descript dog.